2016
DOI: 10.1017/s0007123416000508
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Role of Procedures for Decision Acceptance

Abstract: Procedural fairness theory posits that the way in which authoritative decisions are made strongly impacts people's willingness to accept them. This article challenges this claim by contending that democratic governments can achieve little in terms of acceptance of policy decisions by the procedural means at their disposal. Instead, outcome favorability is the dominant determinant of decision acceptance. The article explicates that while central parts of procedural fairness theory are true, outcome favorability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
182
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(198 citation statements)
references
References 62 publications
13
182
3
Order By: Relevance
“…2. The only other study we have identified that tests the importance of procedures and outcomes for citizens' decision acceptance in a population-based survey stems from Esaiasson et al (2016a). Yet, their survey experiment is limited to the context of metropolitan Gothenburg.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2. The only other study we have identified that tests the importance of procedures and outcomes for citizens' decision acceptance in a population-based survey stems from Esaiasson et al (2016a). Yet, their survey experiment is limited to the context of metropolitan Gothenburg.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental studies on similar topics focus on how various modes of decision making in small-scale settings affect individual assessments of procedural fairness (Tyler 1994;Esaiasson et al 2016b), or decision acceptability (Esaiasson et al 2016a;Arnesen 2017). Previous experimental studies on similar topics focus on how various modes of decision making in small-scale settings affect individual assessments of procedural fairness (Tyler 1994;Esaiasson et al 2016b), or decision acceptability (Esaiasson et al 2016a;Arnesen 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 For recent reviews of the vast procedural fairness literature, see MacCoun (2005) or Murphy (2017), for example. 4 See however, Esaiasson, Persson, Gilljam, and Lindholm (2016). 5 See also Gilley (2006), showing that "general governance" (capturing government effectiveness, control of corruption, and rule of law) emerges as the strongest correlate of state legitimacy.…”
Section: Outcomes Fairness and Political Supportmentioning
confidence: 99%